Volume of water added to crushed ice affects the efficacy of cryotherapy: a randomised, single-blind, crossover trial - de Estefani D. (2020)
© 2019 Chartered Society of PhysiotherapyObjective: To compare the effects of different cryotherapeutic preparations. Design: Randomised, single-blind, crossover trial. Setting: University laboratory. Participants: Sixteen healthy women. Interventions: Participants were randomised to receive three cryotherapeutic preparations: pure ice (500 g), watered ice (500 g of ice in 500 ml of water) and wetted ice (500 g of ice in 50 ml of water). Main outcome measures: The primary outcome was skin surface temperature after cryotherapy, measured at the central point of application, and the minimum temperature of the region of interest (ROI). The secondary outcome was the surface area cooled to <13.6 °C, which is the recommended temperature to achieve therapeutic effects. Results: After application of ice, mean skin surface temperature at the central point was 4.6 [standard deviation (SD) 1.9] °C for the pure ice preparation, 4.9 (SD 2.5) °C for the wetted ice preparation, and 9.6 (SD 1.8) °C for the watered ice preparation. When compared with the watered ice preparation, this represented a mean difference (MD) of 5.0 °C for the pure ice preparation [95% confidence interval (CI) 4.0 to 6.0; P < 0.001] and an MD of 4.7 °C for the wetted ice preparation (95% CI 2.5 to 6.8; P < 0.001). The minimum temperatures in the ROI were also lower for the pure ice preparation 3.0 (SD 0.9) °C and the wetted ice preparation 2.8 (SD 0.6) °C than the watered ice preparation 7.9 (SD 1.5) °C. This represented an MD of 4.8 °C for the pure ice preparation (95% CI 4.0 to 5.7; P < 0.001) and 5.1 °C for the wetted ice preparation (95% CI 4.0 to 6.2; P < 0.001]. Conclusions: Application of pure ice or wetted ice led to a greater decrease in skin surface temperature compared with watered ice. For clinical purposes, combining equal parts of water and ice could decrease this effect. Clinical trial registration number: Clinicaltrials.gov (NCT03414346).